Pediatric B‐Cell Lymphoma With Lymphoblastic Morphology, TdT Expression, MYC Rearrangement, and Features Overlapping With Burkitt Lymphoma. Issue 5 (19th January 2016) - Meznarich, Jessica; Miles, Rodney; Paxton, Christian N.; Afify, Zeinab
Abstract : Burkitt lymphoma (BL) and B‐lymphoblastic lymphoma are subtypes of pediatric non‐Hodgkin lymphoma with different presenting features, treatment, and outcomes. This case report documents a 5‐year‐old female who presented with B‐cell lymphoma with lymphoblastic morphology, terminal deoxynucleotidyl transferase expression, MYC rearrangement, and features overlapping with BL. Genomic microarray analysis identified a gain on the long arm of chromosome 1 without other definitive changes. She was treated according to a BL protocol and remains in remission 16‐months after initial diagnosis.